Respuesta :

Since you are given the value of y in the first equation, you can plug it into the second equation:
[tex]9x-3(3x-4)=14[/tex]

Now we'll solve for x:
[tex]9x-9x+12=14[/tex]
[tex]12=14[/tex]

Since we know that 12 does not equal 14, we can say that:
[tex]12 \neq 14[/tex]

So, there's no x value that satisfies the equation, and hence, there will be no y value. In conclusion, the answer is A, there's no solution.
there is no solution.
y=3x-4
9x-3y=14

substitute the given value of y into the equation 9x-3y=14
9x-3(3x-4)=14

solve the equation for x

the system ends up having no solutions.